Legal Reform of Wastewater Management under the Job Creation Law in Kendari City: Between Regulatory Conflict and Environmental Ethics - Maskun, Maskun; Halim, Hamzah; Mukhlis, Muhammad Mutawalli; Kamaruddin, Hanim; Ratnawati, Ratnawati; Aslan, Jamal; Muchtasar, Rizal; Kapugu, Betsy Anggreni; Allo, Zet Tadung (LAW REFORM, 2025)
Prior to the implementation of the Job Creation Law, wastewater management in Indonesia was governed by the granting of liquid waste management permits. Nevertheless, the implementation of the new law has supplanted these licenses with a technical approval system that mandates adherence to wastewater quality requirements. This study aims to examine the current legal framework governing wastewater management in Indonesia and assess its execution under the Job Creation Law, with a focus on environmental sustainability. The employed methodology is a normative and empirical legal research strategy, utilizing qualitative analysis via document examination and field observation in Kendari City. The findings suggest that the new legislation encounters implementation difficulties, particularly in overseeing wastewater from home and small-scale enterprises, such as laundry services, which are predominantly unregulated. The conclusion is that the existing legal framework has not adequately integrated principles of environmental ethics, including anthropocentrism and ecocentrism. Consequently, legal reform and the establishment of ethical principles are essential to guarantee environmental preservation and foster the sustainability of ecological functions.